2014
DOI: 10.3945/an.114.006783
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-to-Potassium Ratio and Blood Pressure, Hypertension, and Related Factors

Abstract: The potential cost-effectiveness and feasibility of dietary interventions aimed at reducing hypertension risk are of considerable interest and significance in public health. In particular, the effectiveness of restricted sodium or increased potassium intake on mitigating hypertension risk has been demonstrated in clinical and observational research. The role that modified sodium or potassium intake plays in influencing the renin-angiotensin system, arterial stiffness, and endothelial dysfunction remains of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
181
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(199 citation statements)
references
References 54 publications
(209 reference statements)
14
181
1
3
Order By: Relevance
“…These results are consistent with previous studies [32]. The PURE study found that a 1-SD increment in the estimated sodium-to-potassium ratio (SD=3.26) was associated with increments of 2.3 mmHg in SBP and 0.78 mmHg in DBP.…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with previous studies [32]. The PURE study found that a 1-SD increment in the estimated sodium-to-potassium ratio (SD=3.26) was associated with increments of 2.3 mmHg in SBP and 0.78 mmHg in DBP.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the sodium-to-potassium ratio (1.9) exceeded the WHO recommendation of a sodium-to-potassium molar ratio of 1:1 [24]. A recent review demonstrated that in various randomized controlled trials the sodium-to-potassium ratio had a stronger association with BP than sodium or potassium alone [25]. In the development of hypertension, excessive sodium and insufficient potassium intake are both shown to play a role since they result in vascular smooth muscle cell contraction which leads to increased peripheral vascular resistance thus causing high BP [26].…”
Section: Discussioncontrasting
confidence: 44%
“…The mean urinary sodium to potassium ratio was high in this study (3.1 ± 1.3). Multiple other studies have shown stronger correlations between this ratio and the development of hypertension than with either the urinary sodium or potassium alone [21], therefore, this ratio should be taken into consideration in future studies. Most of the study participants were either overweight (41%) or obese (25%).…”
Section: Discussionmentioning
confidence: 99%